E(var)3-9 of Drosophila melanogaster Encodes a Zinc Finger Protein - Weiler, Karen S. (Copyright © 2007 by the Genetics Society of America, 2007)
The importance of a gene's natural chromatin environment for its normal expression is poignantly illustrated when a change in chromosome position results in variable gene repression, such as is observed in position effect variegation (PEV) when the Drosophila melanogaster white (w) gene is juxtaposed with heterochromatin. The Enhancer of variegation 3-9 [E(var)3-9] gene was one of over a hundred loci identified in screens for mutations that dominantly modify PEV. Haploinsufficiency for E(var)3-9 enhances w(m4) variegation, as would be expected from increased heterochromatin formation. To clarify the role of E(var)3-9 in chromosome structure, the gene has been cloned and its mutant alleles characterized. The involvement of E(var)3-9 in structure determination was supported by its reciprocal effects on euchromatic and heterochromatic PEV; E(var)3-9 mutations increased expression of a variegating heterochromatic gene in two tissue types. E(var)3-9 mutations also had a recessive phenotype, maternal effect lethality, which implicated E(var)3-9 function in an essential process during embryogenesis. Both phenotypes of E(var)3-9 mutations were consistent with its proposed function in promoting normal chromosome structure. The cloning of E(var)3-9 by classical genetic methods revealed that it encodes a protein with multiple zinc fingers, but otherwise novel sequence.